Thermalization and non-monotonic entanglement growth in an exactly solvable model - Shruti Paranjape; Nilakash Sorokhaibam (European Physical Journal C: Particles and Fields)
Abstract We study quantum quenches and subsequent non-equilibrium dynamics of free Dirac fermions in 1 + 1 spacetime dimensions using time dependent mass. The final state is a normalized boundary state which is called generalized Calabrese-Cardy (gCC) state and the system thermalizes to a generalized Gibb’s Ensemble(GGE). We can also tune the initial states so that the final states are exact Calabrese-Cardy (CC) state and special gCC states. The system in the CC state thermalizes to a Gibb’s ensemble. We derive closed-form analytic expressions for the growth of entanglement entropy of subsystems consisting of arbitrary number of disjoint intervals in CC state. We show that the entanglement entropy of a single interval grows monotonically before saturation. In case of certain gCC states, for particular charges, the entanglement entropy of a single interval grows non-monotonically when the effective chemical potential is increased beyond a critical value. We argue that the non-monotonic growth of entanglement entropy is a boundary effect which arises due to increase in long range correlation and decrease in short range correlation at early times.